2009
DOI: 10.2355/isijinternational.49.164
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Extraction Kinetics of Titania and Iron from an Ilmenite by H2–Ar Gas Mixtures

Abstract: Reduction of an ilmenite concentrate as a natural concentration containing 49.78 mass% TiO 2 and 27.96 mass% total Fe by H 2 -Ar gas mixtures was investigated from 1 073 to 1 273 K. Both the reduction degree and reduction rate increased with the increase of temperature and hydrogen content. The reduction degree of the ilmenite decreased due to the presence of impurities including manganese and silicon oxides in the ilmenite concentrate. During the reduction, the formation of manganese and silicon oxide-enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The unreacted core shrinking model can be used to describe the reduction kinetics of FeTiO3 by hydrogen. 1,7) According to unreacted core shrinking model, the reduction of FeTiO3 by hydrogen can be approximately divided into three main steps: diffusion of hydrogen in the gas phase boundary; diffusion of hydrogen in the product layer; chemical reaction at the interface. Generally, the first step is not the rate controlling step.…”
Section: Experiments and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The unreacted core shrinking model can be used to describe the reduction kinetics of FeTiO3 by hydrogen. 1,7) According to unreacted core shrinking model, the reduction of FeTiO3 by hydrogen can be approximately divided into three main steps: diffusion of hydrogen in the gas phase boundary; diffusion of hydrogen in the product layer; chemical reaction at the interface. Generally, the first step is not the rate controlling step.…”
Section: Experiments and Proceduresmentioning
confidence: 99%
“…[1][2][3][4][5][6] However, the kinetic mechanism is still unclear. Because the main component of ilmenite is FeTiO 3 , it is important to clear the reduction kinetics of FeTiO 3 first, which is the main aim of the present work.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Shin et al [20] showed that the electronic conductance of TiO 2 particles can be increased by more than one order of magnitude by changing the annealing atmosphere from pure Ar to 95% Ar-5% H 2 . Wang et al [21] indicated that increasing the hydrogen concentration in Ar-H 2 gas mixture is obviously beneficial to the reduction degree of ilmenite. An Ar-H 2 atmosphere has been regarded as a reducing atmosphere for TiO 2 [17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…23,30) In the reduction series, the transformations of Fe 2 O 3 →Fe 3 O 4 and Fe 3 O 4 →FeO are much easier than that of FeO→Fe, thus the two former reactions can be ignored in the kinetics analysis. 31,32) In addition, the water gas shift reaction will also take place besides for the reduction of iron oxides, which will restrict the gas utilization in gas-injection BF. The FeO reduction in the gases mixture and the water gas reaction can be expressed as follows: …”
Section: Kinetic Model For Reduction Of Iron Oxidesmentioning
confidence: 99%